(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ The text addresses the problem of planned obsolescence from the point of view of consumer protection, based on the decisions of AutoritÃ Garante della Concorrenza e del Mercato which condemned Samsung and Apple on the grounds of the prohibition of unfair commercial practices. It aims to consider the scope of the applicable similar norms in Portuguese and Brazilian legal systems. Methodology ”“ Analysis of the grounds relied on those decisions, as well as the relevant doctrine regarding planned obsolescence and consumer protection from a comparative law perspective. Findings ”“ The text demonstrates which norms can ensure consumer protection in the case of technical or functional planned obsolescence, especially considering the communication dimension, which focuses on the right to information.